2019
DOI: 10.1590/1414-431x20198631
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA MEG3 inhibits the growth of hepatocellular carcinoma cells by sponging miR-9-5p to upregulate SOX11

Abstract: The long non-coding RNA (lncRNA) maternally expressed gene 3 (MEG3), a tumor suppressor, is critical for the carcinogenesis and progression of different cancers, including hepatocellular carcinoma (HCC). To date, the roles of lncRNA MEG3 in HCC are not well illustrated. Therefore, this study used western blot and qRT-PCR to evaluate the expression of MEG3, miR-9-5p, and Sex determining Region Y-related HMG-box 11 (SOX11) in HCC tissues and cell lines. RNA pull-down and luciferase reporter assay were used to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“… 23 , 24 For example, lncRNA FAM83H-AS1 is reported to facilitate cell proliferation, migration and invasion in HCC. 25 Liu et al 26 have indicated that lncRNA MEG3 could inhibit cell proliferation and promote cell apoptosis in HCC. A study by Zhang et al 27 has confirmed that lncRNA XIST could promote cell proliferation and migration through targeting PDCD4 in HCC.…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 24 For example, lncRNA FAM83H-AS1 is reported to facilitate cell proliferation, migration and invasion in HCC. 25 Liu et al 26 have indicated that lncRNA MEG3 could inhibit cell proliferation and promote cell apoptosis in HCC. A study by Zhang et al 27 has confirmed that lncRNA XIST could promote cell proliferation and migration through targeting PDCD4 in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…CeRNA network is a typical post-transcriptional regulatory mechanism which has been reported in various cancers, including HCC. For example, lncRNA MEG3 represses HCC cell growth via up-regulating SOX11 through sponging miR-9-5p [ 20 ]. LncRNA miat serves as a ceRNA to modulate sirt1 by acting as a miR-22-3p sponge in HCC cellular senescence [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…23 MiR-9-5p is up-regulated in liver cancer tissues, and consistent with this, miR-9-5p is highly expressed in HCC and the miR-9a-5p mimic significantly increased the proliferation of hepatoma cells and inhibited apoptosis. 24 Therefore, miRNAs are also promising biomarkers for the clinical diagnosis of HCC. 24 NOX is a multimeric transmembrane enzyme complex that produces superoxide anions and hydrogen peroxide from molecular oxygen in response to multiple stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…24 Therefore, miRNAs are also promising biomarkers for the clinical diagnosis of HCC. 24 NOX is a multimeric transmembrane enzyme complex that produces superoxide anions and hydrogen peroxide from molecular oxygen in response to multiple stimuli. The mammalian NOX family includes seven subtypes: NOX1, NOX2, NOX3, NOX4, NOX5, double oxidase 1 and double oxidase 2.…”
Section: Discussionmentioning
confidence: 99%